Money and liberty - Frankel, S. Herbert (Washington, D.C. : American Enterprise Institute for Public Policy Research, 1980)
The book examines the psychological and political foundations of the modern money economy. It also criticizes the neo-Keynesian belief that monetary management is sufficient to prevent its decline. The author lucidly describes the ideological basis of contemporary monetary debates, destroying many of the illusions about money that have led to worldwide inflation. He demonstrates why money, a symbol of trust, cannot continue to be used if it ultimately becomes the symbol of the opposite.
usc 21/6/17
Loans
Keywords: Money; Liberty